ChemInform Abstract: Ammonium Iodide‐Induced Sulfonylation of Alkenes with DMSO and Water Toward the Synthesis of Vinyl Methyl Sulfones. Issue 22 (15th May 2015) - Gao, Xiaofang; Pan, Xiaojun; Gao, Jian; Huang, Huawen; Yuan, Gaoqing; Li, Yingwei
Abstract: The novel and highly stereoselective sulfonylation of olefins with DMSO and H2 O is achieved using NH4 I as promoter to give vinyl methyl sulfones.